UJI DAYA TERIMA KERIPIK DAUN JERUJU DARI TANAMAN JERUJU (Acanthus ilicifolius) DI DESA PALUH MERBAU KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Siti Nurlani Harahap; Lili Noviyanti; Umidin Nurzanah Sembiring (Jurnal Biogenerasi, 2022)
Mangrove forests are the most productive ecosystems in the world that provide many benefits to coastal waters and commercial forest products, protecting the coastline, and supporting coastal fisheries. Mangrove management into the food is still widely unknown by the community, one of them is the management of jeruju into the food ingredients. This study aims to determine the acceptability of jeruju leaf chips derived from jeruju leaves (Acanthus ilicifolius). This study used the Group Randomized Design (RAK) method with treatment, it’s the addition of jeruju leaf extract to the flour dough which consisted of three levels of treatment, they are J1 samples without the addition of jeruju leaf extract, J2 is the addition of 30 grams of jeruju leaf extract and J3 is the addition of 50 grams of jeruju leaf extract. The test of the acceptability of jeruju leaf chips was carried out using an organoleptic test consisting of 20 panelists with a numerical scale of 5 = very like; 4= likes; 3 = rather like (regular); 2= dislike and 1 = strong dislike. From the research conducted, then the average result of the panelist's favorability of the color, texture and brittleness are the panelists prefer samples with J3 treatment (sample with the addition of jeruju leaf extract 50 grams ) with a higher favorability value than the J2 and J3 treatment are 4.15; 4.1 and 4.25. As for the taste and aroma, panelists prefer J1 treatment (without the addition of jeruju leaf extract) with panellist favorability scores of 3.75 and 3.6. As for the J2 treatment, the average panelist doesn't like it